Enhancing Students' Understanding of Aqidah and Akhlak through Differentiated Instruction at MIS Al Badriyah Rarang - Baiq Hayatul Isnaini; Susi Ariana (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students' understanding of Aqidah and Akhlak at MIS Al Badriyah Rarang through the implementation of Differentiated Instruction (DI) as the primary teaching model. Aqidah and Akhlak are essential subjects in Islamic education that focus on the development of correct beliefs and moral values. However, traditional teaching methods often fail to address the diverse learning needs of students, leading to varying levels of comprehension and engagement. Differentiated Instruction offers a solution by tailoring teaching strategies to meet the individual learning needs, preferences, and readiness of each student. The research was conducted with a group of students at MIS Al Badriyah Rarang during the 2024 academic year. The study followed a cyclical process of planning, action, observation, and reflection. Data were collected through pre- and post-assessment tests, classroom observations, and interviews with students and teachers. The objective was to assess the effectiveness of DI in enhancing students’ understanding of Aqidah and Akhlak, while fostering a more inclusive and engaging learning environment. The findings indicate that Differentiated Instruction significantly improved students' engagement and understanding of the subjects. Students who were initially struggling with the material showed notable progress, while those who were already proficient were challenged further through more advanced tasks. Additionally, the DI approach fostered a more positive learning environment where students were encouraged to express their ideas and beliefs, promoting critical thinking and moral reasoning. In conclusion, the implementation of Differentiated Instruction at MIS Al Badriyah Rarang has proven to be an effective method for improving students' understanding of Aqidah and Akhlak. This research suggests that DI can be a valuable teaching strategy in Islamic education to cater to diverse student needs and enhance the learning experience.